Disparities in patient share and characteristics between disease-modifying therapy-treated and -untreated people with multiple sclerosis in Germany: a claims data analysis from 2017 to 2022 - Stratil, Ann-Sophie; Papukchieva, Steffeni; Neß, Nils-Henning; Wolf, Inge; Bayas, Antonios; Flachenecker, Peter; Friedrich, Benjamin (Frontiers in Neurology, 2025)
IntroductionDespite significant advances in multiple sclerosis (MS) treatment, a substantial proportion of people with MS (pwMS) remains untreated with disease-modifying therapies (DMTs). This study aimed to assess the proportion of DMT-untreated pwMS according to clinical and sociodemographic characteristics, the differences in healthcare utilization patterns, including MRI frequency and physiotherapy use, between DMT-treated and DMT-untreated pwMS, as well as to examine the time to first prescription among newly diagnosed pwMS in Germany from 2017 to 2022.MethodsLongitudinal routine data from 4.5 million individuals insured by German statutory health insurance were analyzed. PwMS were identified by ICD-10-GM code G35 in at least two quarters within a calendar year. PwMS who filled a DMT prescription during the observation period were classified as DMT-treated. Newly diagnosed pwMS had no recorded G35 code and DMT prescription in the 2 years prior to initial MS coding. MRI scans and physiotherapy sessions were identified using OPS codes and the German Heilmittelkatalog. Group differences were tested with two-sided χ2-tests and t-tests.ResultsIn total, 45.6% of pwMS were DMT-untreated. DMT-untreated rates were higher in secondary progressive (SPMS) and primary progressive MS (PPMS) than relapsing-remitting MS (RRMS; p < 0.0001). Older pwMS (>45 years) were more frequently DMT-untreated (56.0%) compared to younger pwMS (≤45 years; 27.4%; p < 0.0001). Regional differences ranged from 37.5% in eastern Germany to 54.0% in the south-west. More than half of newly diagnosed pwMS did not receive their first prescription for DMT within 6 months of their initial MS coding, with longer times to first DMT prescription among pwMS with a progressive compared to a relapsing disease onset (p < 0.0001). DMT-untreated pwMS averaged more physiotherapy sessions (DMT-untreated: 23.7, SD 35.0; DMT-treated: 20.2, SD 28.7; p < 0.0001) and less MRI scans (DMT-untreated: 0.8, SD 0.8; DMT-treated: 1.5, SD 0.8; p < 0.0001) annually over the observation period than DMT-treated pwMS.ConclusionThese real-world data offer valuable insights into patient care and treatment allocation.